A study on the relationship between drainage basin's geomorphic parameters and streamflow characteristics - Espino, Armando N.
Developing better methods in prediction and estimation of runoff processes has been the subject of researches of hyrdologists and planners for annual maximum daily streamflow. This thesis is an effort to establish a prediction model by investigating the relationship between geomorphic parameters and runoff processes using regression and correlation analysis.